BIMBINGAN KELUARGA SAKINAH DALAM UPAYA PENCEGAHAN PERCERAIAN DI KABUPATEN MERAUKE DALAM PERSPEKTIF MAQHOSID SYARIAH - Saparudin; Al Abza, M.Thohar; Yulia Rahman, Hendra (Jurnal Hukum Keluarga Islam El-Qisth, 2026)
This study examines marriage guidance programs in Merauke Regency through the perspective of maqāṣid al-sharīʿah. It employs a qualitative phenomenological approach with an ethnomethodological framework to collect and analyze data. Primary data were obtained through observation and in-depth interviews, while secondary data were gathered from scholarly works, including academic journals, books, statistical reports, and online news sources. The collected data were analyzed interpretatively while consistently maintaining the theoretical framework and analytical approach adopted in the study. The findings reveal two main points. First, the Ministry of Religious Affairs of Merauke Regency, through the Islamic Community Guidance Section (Bimas Islam), proactively implements marriage guidance  with two primary focuses: (1) marriage guidance for registered prospective brides and grooms through the Office of Religious Affairs (KUA), and (2) Guidance for School-Age Youth targeting senior high school students and university students. Second, the integration of maqāṣid al-sharīʿah values is implicitly embedded in the Bimwin materials as stipulated in the Technical Guidelines for Marriage Guidance for Prospective Couples. These values aim to prepare families to achieve sakinah (inner peace and spiritual well-being—ḥifẓ al-dīn), develop healthy psychological management and marital dynamics (ḥifẓ al-ʿaql), responsibly fulfill economic needs and manage family finances (ḥifẓ al-māl), understand reproductive health (ḥifẓ al-nafs and ḥifẓ al-nasl), and commit to nurturing a high-quality future generation (ḥifẓ al-nasl).